Estimation of Rivaroxaban Plasma Concentrations in the Perioperative Setting in Patients With or Without Heparin Bridging. (January 2018) - Lessire, Sarah; Douxfils, Jonathan; Pochet, Lionel; Dincq, Anne-Sophie; Larock, Anne-Sophie; Gourdin, Maximilien; Dogné, Jean-Michel; Chatelain, Bernard; Mullier, François
Introduction: Estimation of residual rivaroxaban plasma concentrations may be requested before invasive procedures and some patients at high thromboembolic risk will have a bridging therapy with heparins when rivaroxaban is interrupted. Objective: The objective of this study was to assess the performance of the STA-Liquid Anti-Xa assay (STA LAX) and the low and normal procedures of the Biophen Direct Factor Xa Inhibitors (DiXaI) assay, in patients with and without bridging with low-molecular-weight heparins (LMWHs). Materials and Methods: Seventy-nine blood samples were collected from 77 patients on rivaroxaban at CTROUGH or before an invasive procedure. Rivaroxaban plasma concentrations were estimated using Biophen DiXaI, Biophen DiXaI LOW, and STA LAX and compared to liquid chromatography coupled with mass spectrometry (LC-MS/MS) measurements. Stratifications were performed according to heparin bridging. Results: The Biophen DiXaI LOW and STA LAX showed better correlation with LC-MS/MS measurements than Biophen DiXaI in patients not bridged with LMWH (R: 0.97, 0.96, and 0.91, respectively). However, the performance of Biophen DiXaI LOW and STA LAX decreased when residual LMWH activity was present (R: 0.18 and 0.19 respectively) demonstrating that these tests are not specific to rivaroxaban. Conclusion: In patients not bridged with LMWH, we suggest to use the Biophen DiXaI LOW and STA LAX for the estimation of rivaroxaban concentrations <50 ng/mL. These results should be confirmed on a larger cohort of patients. Patients bridged with LMWH have inaccurate estimates of low levels of rivaroxaban and the 3 assays studied should not be used to estimate if it is safe to perform a procedure.